Effects of Digital Learning Tools on the Academic Performance of Intermediate Pupils - Fronda, Marvelyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of digital learning tools on the academic performance of intermediate pupils in Tomas Claudio Colleges, Morong, Rizal during School Year 2025–2026. It specifically aimed to determine the extent of these effects in terms of learning focus and concentration, class engagement and participation, academic motivation and self-regulation, and collaboration and social interaction. The study utilized a descriptive survey research design with documentary analysis. A total of 212 intermediate pupils served as respondents. Data were gathered using a researcher-made questionnaire-checklist and supported by the pupils’ first and second quarter grades as indicators of academic performance.Findings revealed that most respondents were 9–10 years old, female, middle or eldest children, and belonged to small families with 2–3 siblings. Their parents were mostly college graduates, employed or self-employed. The majority of pupils used digital learning tools daily. Results showed that digital learning tools had a high level of positive effect on the different aspects of learning. However, no significant differences were found based on sex, sibling position, family size, parents’ educational attainment, parents’ occupation, and frequency of use. Age was the only variable that showed a significant difference. The pupils’ academic performance was described as Very Satisfactory. Moreover, no significant relationship was found between the perceived effects of digital learning tools and academic performance.The study concludes that while digital learning tools positively influence learning behaviors, they do not directly determine academic performance. It is recommended that proper guidance, collaboration between teachers and parents, and structured use of digital tools be strengthened.